Fuentes para el estudio de la Guerra de la Independencia. La Europa de 1807-1808 vista por el Embajador austríaco en París: Metternich y sus memorias - Torre Fernández del Pozo, Servando De La (Cuadernos de Historia del Derecho, 2007)
The Spanish Independence war has been studied from strictly Hispanic optics, although in Napoleon’s mind Spain was just a piece of his bigger European project. Metternich’s memories constitute a valuable source for the understanding of the Napoleonic phenomenon.